Fungi associated with galleries of the emerald ash borer. Issue 7 (July 2021) - Held, Benjamin W.; Simeto, Sofia; Rajtar, Nickolas N.; Cotton, Alissa J.; Showalter, David N.; Bushley, Kathryn E.; Blanchette, Robert A.
Abstract: The emerald ash borer (EAB) is an exotic forest pest that has killed millions of ash trees in the United States and Canada, resulting in an ecological disaster and billions of dollars in economic losses of urban landscape and forest trees. The beetle was first detected in Michigan in 2002 and has spread through much of the Eastern and Midwestern U.S., reaching Minnesota in 2009. Since then, it has spread across the state and poses a great risk to the more than 1 billion ash trees in Minnesota. The larval stage of EAB creates wounds on trees as they feed on the inner bark, causing disruption of water and sap flow that results in tree death. The fungal community associated with EAB larval galleries is poorly understood and the role these fungi may play in tree death is not known. This study describes fungi isolated from EAB larval galleries sampled throughout the main geographic areas of Minnesota where ash is affected by EAB. Fungal cultures were identified by extracting genomic DNA and sequencing the ITS region of the rDNA. Results from 1126 isolates reveal a diverse assemblage of fungi and three functional guilds comprised of canker pathogens, wood decay, and entomopathogenic fungi. The most common canker-associated genera were Cytospora followed by Phaeoacremonium, Paraconiothyrium, Coniothyrium, Nectria, Diplodia, and Botryosphaeria. Fungi in the Basidiomycota were nearly all wood decay causing fungi and many were species of pioneer colonizing genera including Sistotrema, Irpex, Peniophora, Phlebia and Ganoderma . Some of these fungi seriously affect urban trees, having the potential to cause rapid wood decay resulting in hazardous tree situations. Several entomopathogenic genera with the potential for biological control of EAB were also isolated from galleries. Purpureocillium was the most commonly isolated genus, followed by Beauveria, Clonostachys, Lecanicillium, Akanthomyces, Cordyceps, Microcera, Tolypocladium, and Pochonia . The results identify important fungal functional guilds that are occupying a new niche in ash trees resulting from EAB and include fungi that may accelerate decline in tree health, increase hazard tree situations, or may provide options for biological control of this destructive invasive insect.